2021
DOI: 10.14202/vetworld.2021.1133-1142
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of the probiotic potential of Lactobacillus isolated from native swine manure

Abstract: Background and Aim: Using antimicrobials as a feed additive in swine production is prohibited because it is a major cause of the emergence of antimicrobial-resistant bacteria. Probiotics such as Lactobacillus spp. are an attractive alternative to reduce antimicrobial resistance and promote swine growth. This study aimed to evaluate the in vitro probiotic properties of Lactobacillus isolated from indigenous swine manure. Materials and Methods: A total of 30 fecal samples from healthy individual indigenous pigs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Second, the observed halos in this study signify a manifestation of alpha hemolysis on blood agar ( Halder et al , 2017 ). Consistent with these findings, prior investigations have reported analogous hemolytic activity in lactic acid bacteria isolated from the gastrointestinal tracts of poultry and swine ( Tuyarum et al , 2021 ; Makzum et al , 2023 ). The degradation of blood agar is posited to be instigated by hemolysin, an enzymatic agent capable of lysing host cells to facilitate the assimilation of ferrous compounds, particularly hemoglobin ( Chen et al , 2018 ).…”
Section: Discussionsupporting
confidence: 82%
“…Second, the observed halos in this study signify a manifestation of alpha hemolysis on blood agar ( Halder et al , 2017 ). Consistent with these findings, prior investigations have reported analogous hemolytic activity in lactic acid bacteria isolated from the gastrointestinal tracts of poultry and swine ( Tuyarum et al , 2021 ; Makzum et al , 2023 ). The degradation of blood agar is posited to be instigated by hemolysin, an enzymatic agent capable of lysing host cells to facilitate the assimilation of ferrous compounds, particularly hemoglobin ( Chen et al , 2018 ).…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, in several LAB species, the D-alanine residue located at the end of the pentapeptide is substituted by D-lactate or D-serine and thus blocking vancomycin binding ( Delcour et al, 1999 ). KEGG analysis showed that L. pentosus L33 encodes a Ddl ligase, responsible for the D-alanine to D-lactate substitution in Lactobacilli ( Tuyarum et al, 2021 ). Furthermore, there are reports that indicate that many LAB genera exhibit intrinsic resistance to other antibiotics, such as bacitracin, kanamycin, teicoplanin, and quinolones ( Imperial and Ibana, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The two H. coagulans strains exhibited a remarkable ability to withstand acidic conditions, with survival rates surging to 300% at pH 3.0 over 3 hours, compared to the control strain, L. plantarum (B-17) isolated from a previous study (Tuyarum et al, 2021). This indicates their aptitude to thrive in low-pH environments.…”
Section: Acid and Bile Salt Tolerancementioning
confidence: 72%
“…The displayed acid and bile salt tolerance has potential industrial applications, given the need for probiotics to survive the stomach's highly acidic environment and colonize within the intestine. The capacity to withstand acidic and saline environments is vital for speci c probiotic bacteria, allowing them to endure extreme conditions and establish themselves within the gastrointestinal tract (Tuyarum et al, 2021). These processes facilitate bacterial respiration by transporting protons, indicating that F0F1-ATPase may elevate the cell's pH in acidic conditions through gene expression regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation